Central extracorporeal life support with left ventricular decompression for the treatment of refractory cardiogenic shock and lung failure - Weymann, Alexander; Schmack, Bastian; Sabashnikov, Anton; Bowles, Christopher T.; Raake, Philip; Arif, Rawa; Verch, Markus; Tochtermann, Ursula; Roggenbach, Jens; Popov, Aron-Frederik; Simon, André R.; Karck, Matthias; et al. (Journal of cardiothoracic surgery, 2014)
The purpose of this prospective study was to evaluate the effects and functional outcome of central extracorporeal life support (ECLS) with left ventricular decompression for the treatment of refractory cardiogenic shock and lung failure.
Gesehen am 23.09.2020